An experimental study of the dynamics of ascent of the bubble system in the presence of a surfactant - Antonnikova Alexandra; Basalaev Sergey; Usanina Anna; Maslov Eugene (MATEC Web of Conferences, 2018)
This paper presents investigations on the new experimental setup for obtaining a compact cluster of monodisperse bubbles of a given diameter is presented. Also we provided the results of experimental study of the bubble cluster floating-up in the presence of a surfactant in a wide range of Reynolds numbers. There was held a comparison of the dynamics of the floating-up of a monodisperse bubble cluster in a glycerol medium and in the medium glycerin supplemented with a surfactant.